Oral manifestations of secondary syphilis in an adult female patient - Deyanira Cabrera Escobar; Luis González Valdés (Centro Provincial de Información de Ciencias Médicas, 2018)
The case report of a 38 year-old patient who was assisted in the stomatological department of "Cuatro caminos" polyclinic is described due to multiple painless lesions in almost all the oral mucous. Keeping in mind these symptoms a recurrent aphthous stomatitis was diagnosed, but the prescribed treatment was not satisfactory. Then a consultation with the specialist in Internal Medicine was carried out, who indicated her complementary exams and, according to the clinical and laboratory criteria, the presence of secondary syphilis was confirmed. The focus control was carried out and the remission of the disease was achieved.